On the stability of a nonic functional equation in quasi-normed spaces - Kim, Soo Hwan (JOURNAL OF ADVANCES IN PHYSICS, 2016)
In this paper, we extend normed spaces to quasi-normed spaces and prove the generalized Hyers-Ulam stability of a nonic functional equation: where $9 ! = 362880$ in quasi-normed spaces.